A potential biomarker for the Permian-Triassic ecological crisis - Grice, Kliti; Twitchett, R.; Alexander, Robert; Foster, C.; Looy, Cindy (Earth and Planetary Science Letters, 2005)
A unique biomarker, a C33 n-alkylcyclohexane (n-heptacosylcyclohexane), which strongly increases in abundance within the extinction interval of the end-Permian ecological crisis, is here reported from the key Permian–Triassic (P–Tr) marine section in Greenland. Prior to this study, this compound had been known from Early Triassic organic-rich marine rocks and oils from the northern Perth Basin, Western Australia for two decades. We have identified the compound in high relative abundance in 29 samples from P–Tr marine sections from two separate paleogeographic localities, from Laurasia and Gondwana. Relative concentrations of the C33 n-alkylcyclohexane show similar changes to the relative abundances of extinct spinose acritarchs (Veryhachium and Micrhystridium) indicating that the source organism of the C33 n-alkylcyclohexane is associated with the depositional environments/facies in which the acritarchs are identified. These organisms probably formed the cornerstone of the unique marine ecosystem that thrived in the extinction aftermath in the Early Triassic Ocean.